Social, professional and discipliner relevance of nursing - Vilchez-Barboza, Vivian (Universidad de Sonora, 2019)
Reflection article, which aims to make a reflection on the social, professional and discipliner relevance to tackle cardiovascular health in the Nursing Intervention in Adult Workers Signature, located in the VII semester of the curriculum of the Nursing career at the University of Costa Rica. It begins with a look at the state of art in Costa Rica, the challenges posed to the health sector cardiovascular diseases and the importance it represents for Nursing incorporate this subject in its curriculum.